Association of insertion/deletion polymorphism of angiotensin-converting enzyme gene with essential hypertension and type 2 diabetes mellitus in Malaysian subjects - Vasudevan, Ramachandran; Ismail, Patimah; Stanslas, Johnson; Shamsudin, Norashikin; Moin, Saidi; Mohd Jas, Rusni (Sage Publications, 2008)
Introduction: The deletion (D) allele of the angiotensin-converting enzyme (ACE) gene has been studied in various populations in relation to hypertension (HTN) and type 2 diabetes mellitus (T2DM) with contradictory results.This study sought to determine the association of insertion (I)/D polymorphism of the ACE gene in hypertensive andT2DM subjects in a Malaysian population.